2003
DOI: 10.1002/jnr.10849
|View full text |Cite
|
Sign up to set email alerts
|

Quinacrine blocks PrP (106–126)‐formed channels

Abstract: We investigated the action of the acridine derivative, quinacrine (QC), which has been shown to act as a noncompetitive channel inhibitor. The main effects of QC are voltage- and concentration-dependent changes in the kinetics of the prion protein fragment (PrP[106-126])-formed cation channels. The current-voltage relationships show that the maximal current (I) was not affected whereas the physiologically important mean current (I') was reduced as a result of changes in channel kinetics. These findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…First, the effects of "antiprion" compounds are clearly species/strain-dependent, in that drugs found to restrain prions in one situation may improve replicative ability in another. Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…First, the effects of "antiprion" compounds are clearly species/strain-dependent, in that drugs found to restrain prions in one situation may improve replicative ability in another. Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…, the possible interactions with neuronal membranes of the oligomers independent from the sequences can be traced to three possible mechanisms: i) specific interaction with the protein entity; ii) unspecific interaction with membranes; iii) formation of membrane pores. Chemicophysical analysis demonstrates the formation of PrP106‐126 oligomers that can disrupt membranes and form channels . In AD, soluble Aβ oligomers were initially considered the precursors of amyloid fibres and although their toxicity was demonstrated , only later were they considered central in AD pathogenesis .…”
Section: Prp106‐126 and The Role Of Oligomers In Pathogenesismentioning
confidence: 99%
“…The molecular mechanism involved in the inhibition of PrP sc formation by quinacrine remains unknown. However, it has been suggested that quinacrine blocks PrP106-126 formed channels (Farrelly et al, 2003). NMR spectroscopic studies indicate that the PLA 2 inhibitor, quinacrine, binds to human prion protein at the Tyr-225, Tyr-226, and Gln-227 residues of helix ␣3 (Vogtherr et al, 2003).…”
Section: E Prion Diseasesmentioning
confidence: 99%